Historical translocations by Māori may explain the distribution and genetic structure of a threatened surf clam in Aotearoa (New Zealand). Issue 1 (December 2018) - Ross, Philip; Knox, Matthew; Smith, Shade; Smith, Huhana; Williams, James; Hogg, Ian
Abstract The population genetic structure of toheroa (Paphies ventricosa ), an Aotearoa (New Zealand) endemic surf clam, was assessed to determine levels of inter-population connectivity and test hypotheses regarding life history, habitat distribution and connectivity in coastal vs. estuarine taxa. Ninety-eight toheroa from populations across the length of New Zealand were sequenced for the mitochondrial cytochromec oxidase I gene with analyses suggesting a population genetic structure unique among New Zealand marine invertebrates. Toheroa genetic diversity was high in Te Ika-a Māui (the North Island of New Zealand) but completely lacking in the south of Te Waipounamu (the South Island), an indication of recent isolation. Changes in habitat availability, long distance dispersal events or translocation of toheroa to southern New Zealand by Māori could explain the observed geographic distribution of toheroa and their genetic diversity. Given that early-Māori and their ancestors, were adept at food cultivation and relocation, the toheroa translocation hypothesis is plausible and may explain the disjointed modern distribution of this species. Translocation would also explain the limited success in restoring what may in some cases be ecologically isolated populations located outside their natural distributions and preferred niches.